The Effect of Organizational Culture, Leadership Effectiveness and Innovative Behavior on Employee Performance with Job Satisfaction as an Intervening Variable at PT. Kemilau Permata Sawit Nagari Kubu Tapan - Rino Esa Maha Putra; John Veri (Jurnal Multidisiplin Sahombu, 2025)
This study aims to examine the extent of the influence of organizational culture, leadership effectiveness, and innovative behavior on employee performance with job satisfaction as an intervening variable at PT. Kemilau Permata Sawit Nagari Kubu Tapan. The data collection method was through surveys and distributing questionnaires, with a sample of 73 respondents. The analysis method used was multiple linear regression analysis and path analysis using SPSS. The results of the study obtained based on the Partial Test (t-Test) obtained a significant influence between Organizational Culture on Job Satisfaction. A significant influence between Leadership Effectiveness on Job Satisfaction. An insignificant influence between Innovative Behavior on Job Satisfaction. An insignificant influence between Organizational Culture on Employee Performance. An insignificant influence between Leadership Effectiveness on Employee Performance. A significant influence between Innovative Behavior on Employee Performance. A significant influence between Job Satisfaction on Employee Performance. The direct influence of Organizational Culture on Employee Performance Employee Performance is smaller than the indirect influence of Organizational Culture on Employee Performance through Job Satisfaction. The direct influence of Leadership Effectiveness on Employee Performance is smaller than the indirect influence of Leadership Effectiveness on Employee Performance through Job Satisfaction. The direct influence of Innovative Behavior on Employee Performance is greater than the indirect influence of Innovative Behavior on Employee Performance through Job Satisfaction.